The Effect of Strong Magnetic Field and Engine Rotation on Fuel Consumption and Exhaust Gas Emissions for Gasoline Engines - Nugraha, Adelansyah; Orhani, Senat (CV. Creative Tugu Pena, 2022)
An Iincreasing number of means of transportation in various cities causes air pollution. There have been many studies to reduce air pollution due to motorized vehicles. One of them relates to the fuel line. The purpose of this study was to determine the relationship between the strength of the magnetic field in the fuel line on fuel consumption and exhaust emissions. The research method uses a pure experimental method. The independent variables are magnetic field strength (51, 102, 152, 202, and 249 gauss) in the fuel line and engine speed (1500 rpm, 2500 rpm, 3500 rpm and 4500 rpm). The dependent variable is fuel consumption (ltr/hour) and exhaust emissions. Test was carried Fourier transform infrared out to determine the chemical compound group of the fuel. The results showed that the highest concentration of transmittance at a wavelength of 2850 cm?¹ - 2970 cm?¹ was 77.75% with a magnetic field strength of 249 gauss, when compared to standard conditions it was 33.05%. At a strong magnetic field of 249 gauss with a rotation of 2500 rpm, it can save fuel consumption of 0.2 liters/hour. In addition, it can also reduce the level of exhaust gas O? by 4.16% (3500 rpm), CO gas by 1.29% (2500 rpm), CO? gas by 5.2% (1500 rpm) and HC gas by 215.66%. (4500 rpm). Keywords: Strong Magnetic, Fuel Consumtion, Exhaust Gas Emissions